2017
DOI: 10.1111/jvs.12508
|View full text |Cite
|
Sign up to set email alerts
|

Grazing moderates increases in C3 grass abundance over seven decades across a soil texture gradient in shortgrass steppe

Abstract: Questions How does long‐term exclusion of cattle grazing influence plant community composition in a semi‐arid grassland? Can spatial variation in the effects of cattle grazing exclusion be explained by variation in soil texture? Location Shortgrass steppe, northeast Colorado, USA, in the North American Great Plains. Method We used 16 long‐term (72 yr) cattle exclosures to examine the effects of grazers on plant communities and evaluate whether grazer effects interact with soil texture. Results Although shortgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 39 publications
7
35
0
2
Order By: Relevance
“…The plant communities of the NGP have undoubtedly evolved in the presence of large grazers (Knapp et al ), and large grazer exclusion or livestock removal in the tallgrass and shortgrass prairie is expected to result in lower annual forb cover compared to grazed sites (Fuhlendorf & Engle ; Valone & Sauter ; Manier & Hobbs ). Our findings are comparable with studies in the shortgrass prairie where livestock removal resulted in heightened forb abundance (Augustine et al ). However, our data suggest that removal may additionally lead to landscape homogenization (evidenced by lower compositional heterogeneity compared to bison treatment).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The plant communities of the NGP have undoubtedly evolved in the presence of large grazers (Knapp et al ), and large grazer exclusion or livestock removal in the tallgrass and shortgrass prairie is expected to result in lower annual forb cover compared to grazed sites (Fuhlendorf & Engle ; Valone & Sauter ; Manier & Hobbs ). Our findings are comparable with studies in the shortgrass prairie where livestock removal resulted in heightened forb abundance (Augustine et al ). However, our data suggest that removal may additionally lead to landscape homogenization (evidenced by lower compositional heterogeneity compared to bison treatment).…”
Section: Discussionsupporting
confidence: 91%
“…However, counter to what would be expected in the mesic tallgrass ecosystem, we did not observe significant differences with livestock retention areas in the dominance of C 4 grasses over C 3 grasses (Knapp et al ; Towne et al ; Fuhlendorf et al ). Similar studies looking at cattle grazing in the shortgrass steppe showed very little functional group difference between grazing treatments in less than 20 years, with functional group shifts not occurring for almost 70 years (Augustine et al ). However, more productive ecotones like the mixed‐grass prairie will likely show these shifts sooner than the arid shortgrass steppe (Huston ), and this is likely reflected in the partial transition observed in our study.…”
Section: Discussionmentioning
confidence: 79%
“…This estimate is coincident with historical accounts indicating this site has been grazed continuously by domestic livestock since the mid to late 1800s [51,52]. Since cattle in this region feed preferentially on C 4 grasses, this gives co-occurring C 3 forbs (many of which are unpalatable) a competitive advantage and allows them to increase their biomass and productivity within the grassland matrix [29,77,78].…”
Section: Discussionsupporting
confidence: 77%
“…This change could lead to increased forage productivity, but could also lead to lower soil water availability (Tietjen et al 2017). Derner et al (2019) found that C stocks did not change even after significant vegetation change (Augustine et al 2017), yet uncertainty remains about soil C changes following vegetation changes due to variable and inadequate understanding of C allocation patterns among dominant grasses (Derner and Schuman 2007).…”
Section: Journal Of Soil and Water Conservationmentioning
confidence: 99%